Technology transfer : law, practice, and precedents - Anderson, Mark (Butterworths, 2003)
Analyses a broad range of 'technology transfer' subjects. This work deals with various categories of intellectual property; the harmonisation of copyright law throughout the European Community; the Competition Act 1998; the European Commission's views on research and development agreements; and the UK tax law and laws in the regulatory field.